Pemanfaatan Teknologi Informasi dan Komunikasi sebagai Media Pembelajaran di SMP Negeri 1 Geger Madiun - Sujoko Sujoko (Universitas Muhammadiyah Malang, 2013)
The aim of research are: to know how this utilazatio of Information and Communication Technology (ICT) as media in learning process at SMP Negeri 1 Geger, to know what are the problems in using of Information and Communication Technology as media in learning process at SMP Negeri 1 Geger, and to know what is the affort that the done to overcome some problems in using the Information and Communication Technology as media in learning process at SMP Negeri 1 Geger. Tthe result of research show (1) The utilazation of Information and Communication Technology (ICT) in learning prcess are maximal (2) the problem in using of Information and Communication Technology (ICT) as media in learning process are: (a) there are some classrooms don’t have LCD and Computer, (b) there is teacher who can’t use Information and Communication Technology well as media in learning process, (c) Teacher seldom write at school’s WEB, (d) Teacher doesn’t use e_mail yet as media in learning process. (3) The problem solving are the computer and LCD in the classroom will be added, the school must give good facility to increase the creativity in using ICT as media in learning process, the school give good facility to teacher write at school’s WEB , make e_mail and use it as media in learning process.